Sur l'impact socio-économique des pandémies en Afrique: Leçons tirées du COVID-19, de la trypanosomiase, du VIH, de la fièvre jaune, du choléra - Kohnert, Dirk (SSOAR, GESIS – Leibniz-Institut für Sozialwissenschaften e.V., 2021)
Abstract: Throughout history, nothing has killed more human beings than infectious diseases. Although, death rates from pandemics dropped globally by about 0.8 % per year, all the way through the 20th century, the number of new infectious diseases like Sars, HIV and Covid-19 increased by nearly fourfold over the past century. In Africa, there were reported a total of 4,522,489 confirmed COVID-19 cases and 119,816 death, as of 23 April 2021. The pandemic impacted seriously on the economic and social sectors in almost all African countries. It is threatening to push up to 58 m people into extreme poverty. However, apart from the African poor, the Covid pandemic also affects the growing African middle class, i.e. about 170 million out of Africa's 1.3 billion people currently classified as middle class. Nearly eight million of may be thrust into poverty because of the coronavirus and its economic aftermath. This setback will be felt for decades to come. Moreover, in recent African History also o
urn:nbn:de:0168-ssoar-73043-8
Keywords: (thesoz)Afrika südlich der Sahara; (thesoz)Epidemie; (thesoz)Infektionskrankheit; (thesoz)sozioökonomische Folgen; (thesoz)Armut; (thesoz)wirtschaftliche Folgen; (thesoz)Entwicklungssoziologie; (thesoz)Postkolonialismus; COVID-19 Pandemie; Corona Epidemie; Gewalt; Afrika-Studien; Medizinethik; politische Ethik